Association between VEGF-A, C and D Expression and lymph Node Involvement in Breast Cancer: A Meta-Analysis. Issue 3 (July 2016) - Su, Fei; Liu, Baoquan; Chen, Mingwei; Xiao, Jianbing; Li, Xuemei; Lv, Xiaohong; Ma, Jing; You, Kai; Zhang, Jianguo; Zhang, Yafang
Background: Metastasis is the primary cause of death in patients with breast cancer. Although VEGF-A, C and D are considered to be prime factors in lymph node metastasis in breast cancer, the published studies have conflicting conclusions. Methods: To resolve this conflict, we conducted a meta-analysis of 37 studies (n = 5, 001 patients) evaluating the correlation between VEGF-A, C and D immunohistochemical expression and lymph node metastasis (LNM). The meta-analysis included 22 studies of VEGF-A, 17 of VEGF-C, and 6 of VEGF-D. The relationships between VEGF-A, C and D and clinicopathological parameters were also examined. Results: The results showed a significant association between VEGF-A or VEGF-C overexpression and LNM (risk ratio [RR] = 1.28 [95% CI 1.04-1.58], p = 0.02; and RR = 1.36 [95% CI 1.07-1.72], p = 0.01, respectively). Subgroup evaluation showed a significant association between VEGF-A, C and D overexpression and LNM when analyses were limited to Asian patients (RR = 1.78 [95% CI 1.28-2.46], p = 0.0005; RR = 1.38 [95% CI 1.04-1.84], p = 0.03, and RR = 2.62 [95% CI 1.35-5.09], p = 0.004, respectively). VEGF-A overexpression was significantly associated with lymph vessel invasion (RR = 1.86 [95% CI 1.33-2.60], p = 0.0003). Overexpression of VEGF-C or VEGF-D was significantly associated with HER-2 positivity (RR = 1.30 [95% CI 1.06-1.59], p = 0.01; and RR = 1.75 [95% CI 1.01-3.03], p = 0.05, respectively). Conclusions: With some limitations, our meta-analysis indicated that VEGF-A and C could predict LNM in patients with breast cancer, particularly Asian patients.